Protective effects of yeast extract against alcohol-induced liver injury in rats - Lin, Zihan; Li, Yongjun; Wang, Man; Li, Huan; Wang, Yihong; Li, Xin; Zhang, Ying; Gong, Di; Fu, Lin; Wang, Siying; Long, Danfeng (Frontiers in Microbiology, 2023)
Oxidative stress, inflammatory response, and gut-liver axis dysbiosis have been suggested as the primarily involved in the pathogenesis of alcoholic liver injury. Previous research established that yeast extract (YE) has antioxidant, immune-boosting or microbiota-regulating properties.However, there is currently lack of information regarding the efficacy of YE on alcoholic liver injury .This study seeks to obtain data that will help to address this research gap using a Wistar male rat experimental model. Histologic and biochemical analysis results showed that the groups treated with both low-dose yeast extract (YEL) and high-dose yeast extract (YEH) had lower degrees of alcoholinduced liver injury. The abundance of Peptococcus and Ruminococcus reduced in the low-dose yeast extract (YEL) group, while that of Peptococcus, Romboutsia, Parasutterella, and Faecalibaculum reduced in the high-dose (YEH) group. Furthermore, Spearman analysis showed that the gut microbes were significantly associated with several liver-related indicators. For the analysis of differential metabolites and enriched pathways in the YEL group, the abundance of lysophosphatidylcholine (16:0/0:0) significantly increased, and then the levels of histamine, adenosine and 5' -adenine nucleotide were remarkedly elevated in the YEH group. These findings suggest that both high and low doses of YE can have different protective effects on liver injury in alcoholic liver disease (ALD) rats, in addition to improving gut microbiota disorder. Besides, highdose YE has been found to be more effective than low-dose YE in metabolic regulation, as well as in dealing with oxidative stress and inflammatory responses.